2017
DOI: 10.1002/jca.21587
|View full text |Cite
|
Sign up to set email alerts
|

The Barcelona Hospital Clínic therapeutic apheresis database

Abstract: The TA database helped us to increase our knowledge about various indications and type of TA procedures that were performed in our current practice. We also believe that this database could serve as a model that other institutions can use to track service metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The explanation to this high number of ECP procedures is because we, as do others, have seen an increase in the number of leukocytapheresis performed in non-cytokine-stimulated donors for different cellular therapy protocols during the last years [13][14][15][16] and ECP is a common procedure in the present day. 33,34 5 | CONCLUSIONS Donor's age, preprocedure CBC data as well as central line used as vascular access were factors associated with CE1 of cells when performing leukocytapheresis in nonmobilized donors for cellular therapy purposes. Knowing these characteristics is helpful in the apheresis unit when designing cellular therapy protocols in order to maximize the collection efficiency of the desired cell, to reduce the quantity of the undesired cell population, and to personalize collection variables for each donor.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The explanation to this high number of ECP procedures is because we, as do others, have seen an increase in the number of leukocytapheresis performed in non-cytokine-stimulated donors for different cellular therapy protocols during the last years [13][14][15][16] and ECP is a common procedure in the present day. 33,34 5 | CONCLUSIONS Donor's age, preprocedure CBC data as well as central line used as vascular access were factors associated with CE1 of cells when performing leukocytapheresis in nonmobilized donors for cellular therapy purposes. Knowing these characteristics is helpful in the apheresis unit when designing cellular therapy protocols in order to maximize the collection efficiency of the desired cell, to reduce the quantity of the undesired cell population, and to personalize collection variables for each donor.…”
Section: Discussionmentioning
confidence: 97%
“…Although this patient population could skew the data, our focus was the analysis of preprocedure characteristics that were associated with the CE1 of cells. The explanation to this high number of ECP procedures is because we, as do others, have seen an increase in the number of leukocytapheresis performed in non‐cytokine‐stimulated donors for different cellular therapy protocols during the last years and ECP is a common procedure in the present day …”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results showed that this new schedule was safe and efficacious . Since the start of the program, the number of ECP procedures per year has increased more than sixfold (from 19 in 2012 to 121 in 2016) . Therefore, we performed this study with the aim of reviewing retrospectively our experience using this new offline ECP schedule for treating patients with acute and chronic GVHD.…”
mentioning
confidence: 99%
“…Mononuclear cell collection with an apheresis device (Cobe Spectra, TerumoBCT) was used from 2007 to 2015, and continuous mononuclear cell collection with a different apheresis device (Spectra Optia, TerumoBCT) was used from 2016 onwards. The quantity of blood to process was calculated to obtain a target of 2 × 10 6 /kg CD34+ cells with use of the CD34+ cell count in peripheral blood sampled immediately before starting the apheresis procedure and the historical CE1 …”
Section: Methodsmentioning
confidence: 99%
“…The quantity of blood to process was calculated to obtain a target of 2 × 10 6 /kg CD34+ cells with use of the CD34+ cell count in peripheral blood sampled immediately before starting the apheresis procedure and the historical CE1. 14…”
Section: Apheresis Proceduresmentioning
confidence: 99%